Influence Of Process Parameters On Carbonization And Activa-tion Of Rice Husk - Yadav, Brahamdeo Kumar; Kumar, Amit (Migration Letters, 2024)
The rice husk is waste generated from milling of paddy and creating environmental concern for it elective disposal. It is a cheap organic source for product like activated carbon. Activated Carbon (AC) is solid, carbonaceous, non-hazardous, and highly porous complex compound produced from carbonization of organic material. The demand of cheap agricultural and industrial waste for effective utilization is growing rapidly. Rice husk, due to its high cellulose and lignin content, can be used as source of activated carbon. In the present study, influence of temperature and time on carbonization of rice husk for production of activated carbon was attempted. The rice husk was carbonized at fixed temperature and time followed by activated process at different temperature and residence time. The carbon di oxide was used as activated agents during activation process. Both the parameters temperature and time found to have significant effect on recovery and surface area. However, the recovery reduced abruptly at elevated temperature. The surface area increases with increase in residence time. Under the study the optimum condition for recovery and surface area was achieved at 900°C and 60 min residence time. The recovery and surface area at optimum conditions were 19.80%, and 589.67m2/g, respectively. The activated carbon was also analyzed for it proximate composition.